HOSPITAL-ACQUIRED INFECTIONS IN COVID-19 PATIENTS AT HOA VANG DISTRICT FIELD HOSPITAL, 2020 (Vietnam Journal of Community Medicine, 2022)
Objective: To determine the rate, distribHAIson, agents and  some related factors of hospital-acquiered infection in patients with COVID-19.Method: A cross-sectional study was conducted on 254 COVID-19 patients.Results: Among 254 patients who were eligible for the research, the rate of hospital-acquiered infection was 7.1%. In which, lung infections accounted for the highest rate (78.3%), followed by sepsis (13.1%), surgical site infections (4.3%), and other infections (4.3%). The most of causative agent is K.pneumoniae (29.6%), followed by A.baumannii (14.8%). In the logistic regression analysis, risk factors of HAIs in COVID-19 patients were blood disease (OR = 1.1; p < 0.05), intensive care (OR = 972.6; p < 0 ,05) and central venous catheter (OR = 19.1; p < 0.05). There was a statistically significant difference (p
Keywords: Hospital-acquiered infection, COVID-19.